The Impact of Blended Collaborative Learning on the English Reading Comprehension - Mohsen Akbari Motlagh; Esmaeil Zaraii Zavaraki; Mehdi Vahedi; Morteza Bakhtiarvand; Yaghub Azizi; Dariush Noroozi (RIRAI Publisher, 2023)
The aim of this research was to examine the impact of blended collaborative learning on Iranian learners’ understanding concept of English texts. Among the statistical population of eighth grade male students in Birjand in the academic year, 2021 which numbered 637 people, 30 students were purposefully separated into two experimental and control groups using the available sampling method. After taking the Oxford Placement Test and the purposeful appointment of learners in experimental and control groups, a pre-test was taken. Students in both groups were trained in English text comprehension techniques and skills for 4 weeks. Analysis of test results showed that students who were taught by the blended collaborative method, compared to students who were taught by the individual blended method, in understanding the concept of English texts, correct understanding and recognition of words and proper vocabulary in order to complete incomplete texts in the post-test and delayed the post-test stages have been performed much better. In understanding the reading of English texts, there was a meaningful difference between the performance of the experimental and control groups in the post-test, but no meaningful difference was obtained in function of the control and experimental groups in the delayed post-test.